Interaction of Agaric Acid with the Adenine Nucleotide Translocase Induces Mitochondrial Oxidative Stress - Chávez, Edmundo (Biochem Res Int, 2020)
Mitochondrial permeability transition is characterized by the opening of a transmembranal pore that switches membrane permeability from specific to nonspecific. This structure allows the free traffic of ions, metabolites, and water across the mitochondrial inner membrane. The opening of the permeability transition pore is triggered by oxidative stress along with calcium overload. In this work, we explored if oxidative stress is a consequence, rather than an effector of the pore opening, by evaluating the interaction of agaric acid with the adenine nucleotide translocase, a structural component of the permeability transition pore. We found that agaric acid induces transition pore opening, increases the generation of oxygen-derived reactive species, augments the oxidation of unsaturated fatty acids in the membrane, and promotes the detachment of cytochrome c from the inner membrane. The effect of agaric acid was inhibited by the antioxidant tamoxifen in association with decreased binding of the thiol reagent eosin-3 maleimide to the adenine nucleotide translocase. We conclude that agaric acid promotes the opening of the pore, increasing ROS production that exerts oxidative modification of critical thiols in the adenine nucleotide translocase.